Analisis Pengaruh Kepribadian Ihsan Terhadap Kecenderungan Akademik Pada Mahasiswa Program Pendidikan UIN Sunan Kalijaga Yogyakarta - Farikoh Farikoh; Miftahun Ni'mah Suseno (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
This research aims to determine the relationship between personality of Ihsan and behavioral tendencies of academic cheating, and to analyze the influence of personality traits of Ihsan towards the tendency af academic cheating behavior. The sample of this research are 146 students in Islamic University in Yogyakarta. This Research uses quantitative methods and datas were revealed by using a summated rating scale and processed by Spearman correlation test and 20 predictor regression test technique. The result of correlation test showed a correlation coefficient of -0.365 with a significance level of 0.000 (p<0.05). It means there is a negative relationship between Ihsan personality and behavioral tendencies of academic cheating. The regression analysis showed the character of constancy, muru'ah, patient, and sincere were the strongest predictors. Keywords : personality, ihsan, academic cheating, students